Fractionation and speciation of metals in lakes formed by abandoned clay pits from industrial effluents (Santa Gertrudes, São Paulo, Brazil) using the diffusive gradient in thin films (DGT) technique - Venciguerra, Lucas Souza [UNESP]; Lima, Guilherme dos Santos [UNESP]; da Silva, Isabella Carvalho Pereira [UNESP]; Gemeiner, Hendryk [UNESP]; Zanatta, Melina Borges Teixeira [UNESP]; Menegário, Amauri Antonio [UNESP] (Elsevier, 2023)
Environmental impacts caused by mining activities (mainly tailings and effluents) are presenting serious challenges for humanity worldwide. In Brazil, clay extraction activities in the Ceramic District of Santa Gertrudes (CDSG) have led to the formation of abandoned drainage wells causing environmental and human health concerns. In the 90's, it was discovered that in one of the production areas, known as the region of the lakes of Santa Gertrudes, several ceramic industries had contaminated lakes created by abandoned clay pits with industrial effluents containing toxic metals. In the present study, analysis of total and dissolved concentrations of Al, Cd, Co, Cu, Mn, Ni, Pb and Zn in the waters of these lakes were combined with the diffusive gradients in thin films (DGT) technique to assess the lability and bioavailability of the target elements, representing one of the first studies to investigate the real environmental impact of contamination caused by ceramic production wastes to an aquatic system. Furthermore, based on the total concentrations and main physicochemical characteristics of each lake, a speciation analysis was performed using the MINTEQ software which data was compared with other surface water systems. The results indicated the presence of metals associated with ceramic residues in total, dissolved and labile fractions. It was verified that Zn, Ni and Cu were the only target metals found in labile form and according to speciation were present in the form of “free” ions, and thus may present risk in terms of bioavailability, although the majority of the total concentrations are within the limits established by the national environmental agency.
Keywords: Ceramic wastes; DGT; Fractionation; ICP-MS; Lability; Metal speciation; Passive sampling